Ways to improve the environmental safety of the urbanized environment in connection with the Covid-19 - Kryvomaz, Тetiana I.; Varavin, Dmytro V. (Kyiv National University of Construction and Architecture, 2020)
Pandemics of the past have caused all major urban transformations and have affected architecture, design, and infrastructure. The built environment is formed under the influence of diseases and precautions designed to ensure the population's health, hygiene, and comfort. Construction trends have always reflected the ability to evolve after the crisis, and in the context of the COVID-19 pandemic, the most vulnerable to the risk of infection was densely populated cities. Creating an environmentally safe environment to withstand epidemics and other possible emergencies requires a radical overhaul of planning theories and new urban space models. It is necessary to increase the spatial functionality and decentralization of megacities by increasing the potential of micromobility and new transport strategies. Emergency modeling with the help of digital technologies allows for creating an operational system of response and forecasting various scenarios of development of ecologically dangerous situations. High-quality criteria for the built environment parameters, which are used in green construction, aimed at preserving human health, are becoming relevant. Strategies include increasing natural light, improving ventilation, eliminating hazards from the air and surfaces, using natural materials, and landscaping. Modern technologies provide various automatic cleaning strategies with the use of built-in devices for sanitary spraying, disinfecting lighting, and temperature treatment of premises, contactless building management technologies.